Factors contributing to the provision of complementary food by fathers to improve the growth of children aged 6-24 months: a cross sectional study - Mukarromah, Nur; Masruro, Wiwi Septa Hakim; Winata, Septian Galuh; Hidayat, Abdul Aziz Alimul; Priyantini, Diah; Prabawati, Chlara Yunita; Rofiqi, Erfan (Jurnal Ners, 2025)
Introduction: Providing complementary foods to children aged 6-24 months has many obstacles that have an impact on the child's growth. So far, the mother has played the most role, fathers tend to pay less attention in giving complementary food. The purpose of this study was to analyze the factors that contribute to the provision of complementary foods by fathers to improve the growth of children aged 6-24 months. Methods: A cross-sectional approach on 366 children aged 6-24 months who were recruited using simple random sampling. The variables consisted of children age, gender, father's age, father's education, father's job, mother's age, mother's education, mother's job dan father's role and the growth of children age 6-24 months. Data was analysis binary logistic regression. Results: The study showed positive father involvement (72%) and normal growth (76.5%). The multivariate analysis show that father's education, father's job, mother's age, mother's education, mother's job and father's role have a significant relationship with the growth chart. Father's role is the most dominant variable because its OR is the highest (p = 0.001; OR = 2.128; CI = 1.263-3.433), which means that a supportive or better father's role will make the provision of complementary food better and improve the child's growth chart. Conclusions: Fathers play an important role to give complementary feeding in children aged 6-24 months. This study is expected to be applied with a wider range of areas in order to obtain comparisons with research that has been done.